Hidroterapi Rendam Air Hangat Lombongo Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Ratnawati Ratnawati; Fadli Husain; Farman Biki (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2021)
Background: Hypertension can be defined as abnormally high blood pressure. One of the recommended treatment measures is through hydrotherapy using water with a temperature not exceeding 37-37.50CObjective: This study aims to determine the effect of blood pressure before and after warm water bath hydrotherapy in patients with hypertensionMethod: quasi-experimental with one group pretest-posttest approach. The population is all people who experience hypertension recorded in the working area of the South Suwawa Health Center, amounting to 150 people with purposive sampling technique so that the number of samples is 30 people.Results: The results showed that after five weeks of treatment there was an effect on blood pressure of hypertensive patients as evidenced by a significant value of 0.000, 0.05 with an average number of hypertensive patients who experienced a decrease in blood pressure, namely 13 people (43.5%).Conclusion: there is an effect of hydrotherapy soaked in warm water of Lombongo on reducing blood pressure in patients with hypertension.